D-dimer sebagai Biomarker Diagnostik Tuberkulosis Paru pada Efusi Pleura: Tinjauan Pustaka - Reza Aditya Digambiro; Florinda Ilona; Julian Chendrasari; Indah Widya Lestari; Edy Parwanto (PT Kalbe Farma Tbk., 2025)
Background: Tuberculosis (TB) remains a major health threat, especially in developing countries. Although the lungs are the most affected organ, systemic manifestations are quite significant. D-dimer, as one of the fibrin degradation products and also an indicator of coagulation activity, has been extensively researched for its predictive and diagnostic value in various diseases. This study aims to assess the effectiveness of D-dimer as a diagnostic biomarker for pulmonary tuberculosis (TB) in patients with pleural effusion compared to those with non-TB pleural effusion. Methods: The study was conducted as an observational case-control on 64 patients with pulmonary TB with pleural effusion were compared to 64 non-TB subjects with pleural effusion. Result: In the TB patient group, 62.5% of patients were smokers, 46.9% of patients had been exposed to TB. Patients were assessed based on the TB symptom scale and with radiological lung examinations, either x-rays or CT scans. D-dimer levels were correlated with the TB severity. D-dimer levels above the threshold value were significantly higher in patients with severe TB symptoms. Conclusion: A direct correlation was observed between the size of radiological lung lesions and D-dimer levels. The average D-dimer level in the control group was 220 ± 60 ng/mL, which increased to 450 ± 90 ng/mL in TB patients with severe lesions.